A proof-of-concept study of cascade screening for Familial Hypercholesterolemia in the US, adapted from the Dutch model - Mary P. McGowan; Marina Cuchel; Catherine D. Ahmed; Amit Khera; William S. Weintraub; Katherine A. Wilemon; Zahid Ahmad (Elsevier, 2021)
Background: The Dutch cascade screening model for FH was the most successful of such programs in the world. It remains unclear whether aspects of the Dutch model (i.e. direct engagement with FH probands and relatives outside usual healthcare settings) are feasible in the US. This is especially important since prior attempts at cascade screening in the US have had very low screening rates (<10% of families screened). Methods: We conducted a multi-site single-arm proof-of-concept study in which the US-based FH Foundation (a 501c3 research and advocacy organization) directly engaged with FH probands and relatives similar to the approach taken by the Dutch "Foundation for Tracing FH." Results: Eleven unrelated probands with genetically confirmed FH were enrolled. Mean age was 43 years; 82% were women, and 82% were of European ancestry. Prior to enrolling into the study, only 2 families (18% screening rate) were screened for FH with both lipid measurements and genetic testing. Two probands declined cascade screening due to fear over genetic discrimination. Nine total relatives engaged with the FH Foundation. Mean age was 43 years and 44% were women. Seven of those relatives (from 6 families; 55% screening rate) consented to be screened for FH with lipid measurement and genetic testing. The two additional relatives - men ages 39 and 49 - agreed to lipid measurements but not genetic testing, each noting he would like to think more about genetic testing. Conclusions: Our proof-of-concept study demonstrates the feasibility of the FH Foundation engaging FH probands and their relatives outside the usual healthcare settings for cascade screening, similar to the Dutch model. We found only 18% of families had already been screened, and after engaging with the FH Foundation, 55% of families were willing to participate in cascade screening. These findings suggest the methods described here may improve cascade screening rates in the US.